ANALISIS TINGKAT KEHILANGAN AIR PADA PERUSAHAAN DAERAH (PERUMDA) TIRTA ALAMI KABUPATEN TANAH DATAR - Candra, Desril; Masril, Masril; Kurniawan, Deddy (Rang Teknik Journal, 2024)
Perumda Tirta Alami, Tanah Datar Regency is trying to improve the drinking water supply system. With efforts to reduce physical water loss. The current percentage of water loss (Non Revenue Water) in the Tirta Alami Regional Company (PERUMDA) drinking water supply system is 40.2%. This is of course below the tolerance standard for PDAM clean water leakage rates nationally according to Minister of Public Works Regulation Number 20/PRT/M/2006, namely a maximum water loss of 20%. Of course, achieving this target is not easy, because in reality analyzing the number of physical leaks in the drinking water supply system is difficult to carry out. The aim of this research is to analyze, develop and determine a strategy for reducing drinking water losses in the PERUMDA Tirta Alami distribution system, Tanah Datar Regency by carrying out analysis on technical aspects using the steptest method. This method is faster and more effective in determining priority areas to look for leak points. The steptest is carried out by installing a portable flow meter on the inlet pipe to record water flow. Then the valves in each section are closed systematically and sequentially. With this method, it will be known for certain which sections are indicated to have the highest water loss. The result of this research is to analyze the reduction in the leak rate from 40.2% to 30.61% by looking for leaks in predetermined zone sections.